Parenting stress after perineal tear during childbirth: the role of physical health and depressive symptoms - Rattaz, Valentine; Cairo Notari, Sarah; Avignon, Valérie; Achtari, Chahin; Horsch, Antje (Frontiers in Psychology, 2025)
IntroductionThis study investigates the impact of the severity of perineal tear during childbirth on parenting stress at 10–12 weeks postpartum. Studies have shown that up to 80% of primiparous mothers may suffer a perineal tear, which can have important physical and psychological consequences. As the adjustment to parenthood can be highly demanding and stressful for primiparous parents, we hypothesized that having experienced a perineal tear during childbirth could be an additional stressor reducing the resources to cope, which could increase parenting stress. We also hypothesized that this increase in parenting stress could be explained by the consequences of the perineal tear on mothers’ physical health and depressive symptoms.MethodsThis study included 155 primiparous mothers with various degrees of perineal tear (from an intact perineum to a 4th degree tear).ResultsResults showed that perineal tear was not directly associated with parenting stress at 10–12 weeks postpartum. However, we found an indirect pathway of influence through mothers’ physical health and depressive symptoms. Higher degrees of perineal tear were associated with worse physical health in mothers causing an increase in depressive symptoms that, in turn, was associated with higher parenting stress.DiscussionThe results indicate that perineal tear is indirectly associated with parenting stress, through its influence on physical health and depressive symptoms. Therefore, it seems crucial to focus on managing the physical consequences of perineal tear in the first weeks postpartum, to avoid detrimental consequences on mothers’ mental health and parenting.